2016
DOI: 10.1002/sia.5983
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion properties of plasma electrolytic oxidation coated AA7075 treated using an electrolyte containing lanthanum‐salts

Abstract: Plasma electrolytic oxidation (PEO) is a very promising process that can enhance the corrosion and wear resistance by producing a relatively thick, dense and hard oxide ceramic coating on light alloys. The improvement in the corrosion behaviour of the treated metals strongly depends on some process parameters: current density, voltage, treatment time and electrolyte composition. In particular, the addition of additives in the electrolyte produces significant changes in the corrosion behaviour. The use of rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…It can be seen from Figure 10 a that the coating exhibited high total impedance at the beginning of immersion, which indicated that the coating owned high corrosion resistance. Figure 10 d is characterized by a capacitive loop in high and medium frequency ranges, and an inductive loop in the low frequency range, which was similar to the previous reports [ 35 , 36 ]. The appearance of capacitive loop is owing to the charge transfer process, whereas the inductive loop is related to the dissolution of Mg and is indicative of pitting corrosion of the substrate [ 37 , 38 ].…”
Section: Resultssupporting
confidence: 88%
“…It can be seen from Figure 10 a that the coating exhibited high total impedance at the beginning of immersion, which indicated that the coating owned high corrosion resistance. Figure 10 d is characterized by a capacitive loop in high and medium frequency ranges, and an inductive loop in the low frequency range, which was similar to the previous reports [ 35 , 36 ]. The appearance of capacitive loop is owing to the charge transfer process, whereas the inductive loop is related to the dissolution of Mg and is indicative of pitting corrosion of the substrate [ 37 , 38 ].…”
Section: Resultssupporting
confidence: 88%
“…The high resolution Si 2p peak is shown in Figure 13(b). It resulted from the sum of two peaks: the one situated at 101.8 eV BE attributed to the alpha Mg 2 SiO 4 and the one at 102.9 eV BE corresponding to gamma Mg 2 SiO 4 [15]. For each of these two peaks, also the two components 2p 3/2 and 2p 1/2 are shown in the figure.…”
Section: Mg 2smentioning
confidence: 99%
“…The use of rare earth metals salts in the PEO process has been already reported in literature. In detail, one work reported the direct dissolution of lanthanum compounds in the electrolyte used to produce PEO coatings [15] and particles of insoluble cerium oxide were also used suspended in the electrolyte to obtain their coprecipitation during PEO process and improve the properties of the oxide layer [16,17]. Cerium salts were also used to produce solutions used as posttreatment to seal the characteristic pores on coatings obtained by PEO [18].…”
Section: Introductionmentioning
confidence: 99%
“…Other ways of modifying the surface are ion implantation [26][27][28][29][30][31], electrophoretic deposition [32], and laser surface treatment [33][34][35][36]. Development of materials engineering and technology in the following years has allowed new challenges to be posed regarding surface engineering, including, but not limited to, fabrication of porous coatings by the Plasma Electrolytic Oxidation (PEO) or Micro Arc Oxidation (MAO) [37] on light metals and alloys, such as aluminum [38][39][40][41][42][43][44] and its alloys [45][46][47][48][49][50][51][52][53][54], magnesium [38,39,[55][56][57] and its alloys [58][59][60][61][62][63][64], titanium and its alloys [57,[65][66][67][68][6...…”
Section: Introductionmentioning
confidence: 99%